2022
DOI: 10.3390/cells11030401
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicity of Furfural Acetone in Meloidogyne incognita and Caenorhabditis elegans

Abstract: Furfural acetone (FAc) is a promising alternative to currently available nematicides, and it exhibits equivalent control efficiency on root-knot nematodes with avermectin in fields. However, its effect on the reproduction of root-knot nematode is poorly understood. In this study, the natural metabolite FAc was found to exhibit reproductive toxicity on Meloidogyne incognita and Caenorhabditis elegans. The number of germ cells of C. elegans was observed to decrease after exposure to FAc, with a reduction of 59.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…No such coincidence was observed in the F7 treatment group, suggesting that F7 might have a different toxicity mechanism. Several mechanisms underlying reproductive toxicity in C. elegans have been reported, including disruption of the collagen biosynthetic pathway, induction of increased autophagy and reactive oxygen species, and impaired and/or retarded gonad development and decreased brood size caused by germ cell apoptosis, germ cell DNA damage, and oxidative stress. Further toxicological and molecular studies are needed to reveal the mechanisms underlying the reproductive toxicity of F-free formulations in C. elegans , particularly for F2 and F7.…”
Section: Resultsmentioning
confidence: 99%
“…No such coincidence was observed in the F7 treatment group, suggesting that F7 might have a different toxicity mechanism. Several mechanisms underlying reproductive toxicity in C. elegans have been reported, including disruption of the collagen biosynthetic pathway, induction of increased autophagy and reactive oxygen species, and impaired and/or retarded gonad development and decreased brood size caused by germ cell apoptosis, germ cell DNA damage, and oxidative stress. Further toxicological and molecular studies are needed to reveal the mechanisms underlying the reproductive toxicity of F-free formulations in C. elegans , particularly for F2 and F7.…”
Section: Resultsmentioning
confidence: 99%
“…Many PGPR strains have been used effectively to treat RKNs [ 47 ]. Effective and safe RKN disease control techniques are desperately needed in greenhouses [ 48 , 49 ]. C. beijerinckii Sneb518 isolates were selected for further study from 712 bacterial strains found to be effective against RKNs.…”
Section: Discussionmentioning
confidence: 99%
“…B. xylophilus was maintained at 28°C on potato dextrose agar (PDA) medium and fed with Botrytis cinerea . C. elegans and B. xylophilus were synchronized as previously described ( 46 ), and the synchronized nematodes were used in subsequent experiments. M. incognita was maintained on the roots of tomato ( Solanum lycopersicum ) and grown in a greenhouse at 25°C ± 1°C.…”
Section: Methodsmentioning
confidence: 99%